Effects of Liquid Sulfur Fertilizer and Azolla Application on the Growth and Yield of Bird’s Eye Chili (Capsicum frutescens L.) - Waruwu, Frengky Perlindungan; Berliana, Yunida; Kurniawan, Dedi (Agroprimatech, 2025)
This research was carried out at the UPTD BIH Gedung Johor, Medan Johor, Medan City, starting from December 2023 to March 2024. This research aimed to determine the effect of applying liquid sulfur fertilizer and Azolla on the growth and production of cayenne pepper plants. This research used a factorial randomized block design (RAK) with 2 treatment factors. The first factor is liquid sulfur with the symbol (S) which consists of 3 treatment levels, namely: S0 = without sulfur fertilizer, S1 = 2.5 cc/liter of water, and S2 = 5 cc/liter of water. The second factor is Azolla with the symbol (A) which consists of 4 treatment levels, namely: A0 = Without Azolla, A1 = 20 grams/plant, A2 = 40 grams/plant, A3 = 60 grams/plant. The parameters observed in this study were plant height (cm), stem diameter (mm), flowering age (days), number of branches (branches), number of fruits per plant (fruit), fruit weight per plant (grams), number of per plot (fruit), fruit weight per plot. The results showed that liquid sulfur fertilizer treatment had no significant effect on all parameters. Giving Azolla had a significant effect on plant height at 2 WAP, 4 WAP, and some branches. The interaction between the two has no significant effect on all parameters. The best fruit weight per plant was obtained in the combination of S2A2 treatment (Liquid Sulfur 5 cc/liter of water + Azolla 40 grams/plant), namely 125.35 grams. Kata kunci: Sulfur Cair, Azolla, Cabai Rawit.